Determination of vitamin A content from selected Nigerian fruits using spectrophotometric method (Bangladesh Journal of Scientific and Industrial Research, 2017)
The vitamin A content of the fresh fruits was determined by the extraction and quantitative determination of the pro-vitamin A carotenoid-?-carotene. The Retinol Equivalent (RE) was then obtained using standard conversion formula. The result indicated that the fruit with the minimum vitamin A content and percentage among the six samples was found in mango 301.61 ± 1.03 (7%), which was followed closely by watermelon 350.12 ± 19.01 (8%), guava 504.1 ± 0.75 (11%), tomato 542.86 ± 20.20 (12%), pawpaw 683.93 ± 5.15 (16%) and the highest content was found in carrot 2054.10 ± 1.28 (46%) in (RE/100 g). Statistical calculations and analysis showed that there was significant difference in vitamin A content among the fruits (p